Synthesis, Characterization and Antibacterial Activity of a New Series of s-Triazines Derived with Quinolines - J. J. Vora; S. B. Vasava; Asha. D. Patel; K. C. Parmar; S. K. Chauhan; S. S. Sharma (E-Journal of Chemistry)
8-Hydroxy quinoline was synthesized using Skraup reaction. This was condensed with trichloro-s-triazine. The product of the above reaction was allowed to react with triazole derivative. Finally, urea derivatives were allowed to react and the products were characterized by conventional and instrumental methods. Their structures were determined and important biochemical properties were studied